Manajemen Peserta Didik dalam Meningkatkan Mutu Pendidikan di Madrasah Muallimin Muallimat 6 Tahun Bahrul Ulum - Subhan, Mohammad; Sirojudin, Didin (AS-SABIQUN, 2023)
Student management is the only component of school management that determines student activities, which ranges from student entry to students who transfer or leave educational institutions. One aspect under school management that plays an important role in increasing student motivation so as to improve the quality of education is student management. The aim of the study was to determine the management of students in improving the quality of education at Madrasah Mu'allimin Mu'allimat 6 Years Bahrul Ulum. The research was carried out using a descriptive qualitative approach. Types and sources of data used are secondary data and primary data. Researchers used interview techniques, observation and documentation for data collection techniques. In addition, the data analysis technique used is data reduction, data presentation and drawing conclusions. The results of the research that has been carried out are student management in improving the quality of education in Madrasahs through student recruitment, student coaching and management of expenses and alumni. Student management has gone well in implementation so as to improve the quality of education at Madrasah Mu'allimin Mu'allimat 6 Year Bahrul Ulum.